2018
DOI: 10.1159/000489933
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in a Lagos Facility: Implications for the Institution of a Cancer Screening Programme

Abstract: Objective: There are significant epidemiological and biological differences between breast cancer in blacks and whites which have wide-reaching implications for the institution of an effective cancer screening programme in Nigeria. The aim of this study was to describe the clinicopathologic features of breast cancer diagnosed in our facility and to discuss their implications for cancer screening. Methods: A retrospective review of the forms, slides, and results of breast cancer cases received in our facility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In the 18 to 39 age group, a notable difference in both sexes, prostate cancer is not seen, breast cancer still dominates, while cervical cancer occupies the 7th position and ovarian cancer is in the first ten. The dominance of breast cancer in this age range is keeping with the widely reported low mean age of occurrence in Nigeria [29,39,40]. In males 18 to 39, soft tissue, head and neck lymphohematopoietic, and colorectal are dominant while breast, skin, cervix and soft tissue are dominant in females.…”
Section: Discussionsupporting
confidence: 79%
“…In the 18 to 39 age group, a notable difference in both sexes, prostate cancer is not seen, breast cancer still dominates, while cervical cancer occupies the 7th position and ovarian cancer is in the first ten. The dominance of breast cancer in this age range is keeping with the widely reported low mean age of occurrence in Nigeria [29,39,40]. In males 18 to 39, soft tissue, head and neck lymphohematopoietic, and colorectal are dominant while breast, skin, cervix and soft tissue are dominant in females.…”
Section: Discussionsupporting
confidence: 79%
“…Myths about breast cancer still abound among Nigerians, uneducated and educated, because according to Anyanwu et' al missed opportunities for breast cancer education fuel them [2]. The generally young populations in sub-Saharan Africa are reflected in the low mean ages of breast cancer patients for instance, 44 years was reported by Anyanwu et al South east Nigeria, 49 years by Ikeri et al in Lagos Nigeria [3] and 46 years by Anakwenze et al in Botswana [4]. There is a high rate of surgical treatment for breast lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of 43.89 and peak age incidence of 31-50 years are similar to previous reports from Nigeria 12 . Generally, it has been reported that breast cancer presents much earlier in Nigeria and most other African countries than it does in the Western population 13,14 . Most of the patients (80.9%) had painless breast lump as the first symptom.…”
Section: Discussionmentioning
confidence: 98%